Analysis of Frontal Sinuses for Personal Identification in a Chinese Sample Using a New Code Number. Issue 1 (25th July 2019) - Cameriere, Roberto; Scendoni, Roberto; Lin, Zitong; Milani, Chantal; Palacio, Luz Andrea Velandia; Turiello, Marika; Ferrante, Luigi
Abstract: The study of frontal sinuses for personal identification is a considered approach in the forensic field. In Yoshino's system, the frontal sinus patterns of a given person were formulated as a code number (codY) obtained by arranging the class numbers in each classification item. The aim of this work was to use a new code number (codC) with eight digits that includes other two continuous variables obtained as ratios SOR1 (left frontal sinus area/left orbit area) and SOR2 (right frontal sinus area/right orbit area), comparing the results with that of Yoshino. Digital radiographic images of the skulls of 150 Chinese people were analyzed. Spearman's partial correlation coefficients were evaluated between variables characterizing frontal sinus patterns. We used a maximum‐weight dependence tree for statistical analysis. Results demonstrated that codC significantly reduced the probability of having the same personal code number compared with codY. Our scientific approach results valid for personal identification purposes.